Genetic and management adaptation of field bean (Vicia faba L.) in Finland - Seppo Pulli; Mauritz Vestberg (Agricultural and Food Science, 1981)
The investigation of field bean adaptation in Finnish climatic conditions was carried out at the University of Helsinki in 1976—77. The main objectives were to study the effects of seeding time and population density on the quantity and quality of the yield and the vegetative features in the development of two different types of field bean varieties. Field bean yielded 4061 kg/ha in 1976. In 1977only 2042kg/ha was harvested due to the lack of light during the grain filling period and the presense of plant diseases. Delayed seeding lowered yields in both years. Maximum yield was obtained with the seed rate of 240 kg/ha. Two weeks delay in the seeding speeded up flowering by two days. Temperature sum in degree days from seeding to emergence was 140—170°C, from seeding to flowering 618—637°C and from seeding to maturity 1670—1890°C. LAI was 5.7 for early variety and 4.3 for late variety at the time of pod setting representing very effective situation for CGR. Number and distribution of internodes, pods and seeds were primarily influenced by population density and secondly by the differences between varieties.